The consolidation of the afforested agricultural land - Malashevskyi, M.; Malashevska, О. (Land Management, Cadastre and Land Monitoring, 2022)
The article addresses the question of the optimization of forest and agricultural land tenure in the environment of natural afforestation in accordance with the aims of sustainable development. The topicality of the research is predefined by the need for the increase of areas occupied by forests according to the legislative initiatives, need for the improvement of agricultural land, the improvement of ecology in the environment of insufficient afforestation. The resolving of the problem of self-afforested agricultural land plots in the process of land consolidation has been suggested. Approaches to the problem of natural agricultural land afforestation have been singled out, advantages and perspectives of land consolidation as compared to other approaches have been substantiated. The involvement of land plots defined as escheated inheritance and non-recalled land shares to the process of land reallotment at land consolidation has been suggested. The adjustment of the land reallotment methodology at land consolidation in the environment of natural afforestation of agricultural land has been suggested. As the result of reallotment, trees were kept on the afforested land plots, a joint consolidated forest mass was formed, the configuration of land plots was improved, road network was improved. The results can be used at the implementation of the Large-scale Afforestation of Ukraine environmental initiative, and in the following scientific research on land tenure and use spatial improvement.Key words: land afforestation, land consolidation, land plot exchange, land reallotment, agricultural land.